2010
DOI: 10.1080/12297119.2010.9707344
|View full text |Cite
|
Sign up to set email alerts
|

Typology of Korean Eco-sumers: Based on Clothing Disposal Behaviors

Abstract: Green or an εnvironmental consciousnεss has been a major issue for businesses and government offices, as well as consumers, worldwide. In response to this movement, the Korean government announced, in the early 2000s, the era of "Greεn Growth" as a way to encourage green-related business activities. The Korean fashion industry, in various levels of involvement, presents diverse eco-friendly products as a part of the green movement. These apparel products include organic products and recycled clothing. For thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…This insider perspective is useful for understanding the importance of context, as well as the transition that takes place when implementing SF behaviours. Other studies focus on specific practices amongst consumers such as avoiding fast fashion (Kim et al , 2013), relationship formation between wearers and designers (Clarke and Holt, 2016), clothes swapping (Rathinamoorthy et al , 2017), second-hand and vintage shopping (Cervellon et al , 2012; Cassidy and Bennett, 2012; Xu et al , 2014; Reiley and DeLong, 2011; Ryding et al , 2017) and clothing disposal behaviours (Sung and Kincade, 2010; Goworek et al , 2013; Yee et al , 2016). However, this is still a limited field with few studies providing generalisable insights.…”
Section: Sustainable Fashion: a Radical View On Production And Consum...mentioning
confidence: 99%
“…This insider perspective is useful for understanding the importance of context, as well as the transition that takes place when implementing SF behaviours. Other studies focus on specific practices amongst consumers such as avoiding fast fashion (Kim et al , 2013), relationship formation between wearers and designers (Clarke and Holt, 2016), clothes swapping (Rathinamoorthy et al , 2017), second-hand and vintage shopping (Cervellon et al , 2012; Cassidy and Bennett, 2012; Xu et al , 2014; Reiley and DeLong, 2011; Ryding et al , 2017) and clothing disposal behaviours (Sung and Kincade, 2010; Goworek et al , 2013; Yee et al , 2016). However, this is still a limited field with few studies providing generalisable insights.…”
Section: Sustainable Fashion: a Radical View On Production And Consum...mentioning
confidence: 99%
“…Second, this study considers the influence of product and personal characteristics on consumer disposal decisions, which did not receive much attention in past literature. Third, the extant literature on consumer product disposal behaviors focused mostly on garments (Birtwistle & Moore, 2007; Morgan & Birtwistle, 2009; Sung & Kincade, 2010) but paid less attention to other consumer products such as mobile phones and sunglasses, both of which are considered in the current study. The inclusion of more than one product category in the research helps us study different disposal preferences across product categories.…”
Section: Introductionmentioning
confidence: 99%
“…On the consumption side, there is a growing interest in green products in South Korea. World research (2005) showed that 58% South Korean consumers are interested in green products and 76% would like to purchase green products although the price is slightly higher than similar products (cited in Sung and Kincade, 2010). Korean fashion companies are striving to meet consumer needs related to the current green movement.…”
Section: ! Overview Of the South Korean Fashion Industrymentioning
confidence: 99%